Desafios da educação profissional e tecnológica : a experiência do curso superior de tecnologia em gestão de turismo do IFS - Picanço, Cristiane Santos (2011)
This research studies the Technological Undergraduate Course of Tourism Management from the Federal Institute of Education, Science and Technology of Sergipe IFS, analyzing its proposal and the relation between this and the job world. In order to accomplish this objective, others were chosen, such as: contextualize the historical elements which guide the professional and technological education in Brazil and their influences in the conceptions of the technological courses; identify the profile of the Technological Undergraduate Course of Tourism Management at IFS; understand the perceptions of professional and technological education present in the course, as well as the competences developed throughout the course; analyze the idea of formation and the effectiveness of the course s proposal. The main authors who gave support to the study were: Enquita (1989; 1993), Frigotto (1995; 1998; 2005); Harvey (2003), Kuenzer (1999; 2000; 2010), Machado (1991; 2009; 2010), Mello (2007), Saviani (1994; 2004; 2008), Deluiz (2009), Ramos (2001), Brandão (2009; 2010), Bastos (2010), Lima Filho ( 2010), Ciavatta ( 2005; 2010). The empirical field of this study involved IFS and the Tourism Job Market, this last one being represented by hotels, tour agencies and restaurants. The research was conducted in Aracaju, Sergipe, from March 2009 to March 2011, having fifty participants: teachers, students, former students, IFS managers and job market managers. It is a qualitative investigation, with a brief quantitative analysis. It is inspired in the principles of dialectics, which is connected to the philosophical brand of the historical materialism. It is a case study, conducted as an exploratory research, in which structured interview and documental analysis were used as data collection procedures. The results point to the difficulty in recognizing the Technological Course of Tourism as such both by IFS and by the job market. In the first case, it was noted that there is a certain resistance on the part of the institution due to the nature of the course, since this one differs from the teaching culture of the Engineering and Exact Sciences courses. Besides, there is a lack of debate on the technological depth in the Course as well as on the dialect relation between job and education, not to mention the lack of investment in the teachers education concerning the teaching in professional education. In the second case, it was noticed the lack of knowledge concerning the technological under graduate courses, the lack of public policies of Tourism for the value of the tourism profession, besides the fact of the occupation in the area of Tourism not being valued enough by the managers of the job market in Aracaju.